Consequences of COVID-19 on adolescents in Arizona: A longitudinal study protocol - Leybas Nuño, Velia; Mantina, Namoonga M.; Dawodu, Oriyomi; Dykinga, Maureen; Carr, Dametreea L.; Pogreba-Brown, Kristen; Cordova-Marks, Felina; Jehn, Megan; Peace-Tuskey, Kimberly; Barraza, Leila; Garcia-Filion, Pamela (Frontiers in Public Health, 2022)
We developed a five-year prospective cohort study designed to generate actionable community-informed research about the direct and indirect consequences of COVID-19 on adolescents ages 12-17 years in Arizona. Data is collected using an online survey with plans to integrate qualitative data collection methods. The survey is administered at baseline, 4 months, and 8 months in year one, and annually in years two through five. The investigative team uses a multilevel mentoring infrastructure comprised of 19 members including 6 faculty (1 Indigenous, 2 Latinx, and 3 White) from two of three Arizona universities, 8 graduate students (2 Indigenous, 2 White, and 4 Black), and 7 undergraduate students (3 More than one race and 5 Latinx). This study is informed by Intersectionality Theory, which considers the diverse identities adolescents have that are self and socially defined and the influence they have collectively and simultaneously. To this end, a sample of variables collected is race/ethnicity, language usage, generational status, co-occurring health conditions, and gender. Additional measures capture experiences in social contexts such as home (parent employment, food, and housing security), school (remote learning, type of school), and society (racism). The study has two primary outcomes: 1. acute and long-term outcomes of COVID-19 illness and 2. mental health (depressive symptoms and anxiety). Lessons learned from the first 9 months and future plans are discussed.